How to adjust the expected waiting time to improve patient’s satisfaction? - Hui Zhang; Wei-Min Ma; Jing-Jing Zhu; Li Wang; Zhen-Jie Guo; Xiang-Tang Chen (BMC Health Services Research, 2023)
Abstract Background Long waiting time in hospital leads to patient’s low satisfaction. In addition to reducing the actual waiting time (AWT), we can also improve satisfaction by adjusting the expected waiting time (EWT). Then how much can the EWT be adjusted to attribute a higher satisfaction? Methods This study was conducted though experimental with hypothetical scenarios. A total of 303 patients who were treated by the same doctor from August 2021 to April 2022 voluntarily participated in this study. The patients were randomly divided into six groups: a control group (n = 52) and five experimental groups (n = 245). In the control group, the patients were asked their satisfaction degree regarding a communicated EWT (T0) and AWT (Ta) under a hypothetical situation. In the experimental groups, in addition to the same T0 and Ta as the control group, the patients were also asked about their satisfaction degree with the extended communicated EWT (T1). Patients in five experimental groups were given T1 values with 70, 80, 90, 100, and 110 min respectively. Patients in both control and experiment groups were asked to indicate their initial EWT, after given unfavorable information (UI) in a hypothetical situation, the experiment groups were asked to indicate their extended EWT. Each participant only participated in filling out one hypothetical scenario. 297 valid hypothetical scenarios were obtained from the 303 hypothetical scenarios given. Results The experimental groups had significant differences between the initial indicated EWT and extended indicated EWT under the effect of UI (20 [10, 30] vs. 30 [10, 50], Z = -4.086, P < 0.001). There was no significant difference in gender, age, education level and hospital visit history (χ 2 = 3.198, P = 0.270; χ 2 = 2.177, P = 0.903; χ 2 = 3.988, P = 0.678; χ 2 = 3.979, P = 0.264) in extended indicated EWT. As for patient’s satisfaction, compared with the control group, significant differences were found when T1 = 80 min (χ 2 = 13.511, P = 0.004), T1 = 90 min (χ 2 = 12.207, P = 0.007) and T1 = 100 min (χ 2 = 12.941, P = 0.005). When T1 = 90 min, which is equal to the Ta, 69.4% (34/49) of the patients felt “very satisfied”, this proportion is not only significantly higher than that of the control group (34/ 49 vs. 19/52, χ 2 = 10.916, P = 0.001), but also the highest among all groups. When T1 = 100 min (10 min longer than Ta), 62.5% (30/48) of the patients felt “very satisfied”, it is significantly higher than that of the control group (30/ 48 vs. 19/52, χ 2 = 6.732, P = 0.009). When T1 = 80 min (10 min shorter than Ta), 64.8% (35/54) of the patients felt “satisfied”, it is significantly higher than that of the control group (35/ 54 vs. 17/52, χ 2 = 10.938, P = 0.001). However, no significant difference was found when T1 = 70 min (χ 2 = 7.747, P = 0.052) and T1 = 110 min (χ 2 = 4.382, P = 0.223). Conclusions Providing UI prompts can extend the EWT. When the extended EWT is closer to the AWT, the patient’s satisfaction level can be improved higher. Therefore, medical institutions can adjust the EWT of patient’s through UI release according to the AWT of hospitals to improve patient’s satisfaction.